2016
DOI: 10.1007/s13205-015-0335-0
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and biodegradation of remazol reactive dyes by Clostridium species

Abstract: Decolorisation and biodegradation efficacy of potential strains isolated from dyeing effluent collected from Tirupur region, Tamil Nadu, India were studied in remazol reactive dyes. Two potential strains Clostridium butyricum (EI05) and Clostridium acetobutylicum (EI25) identified by biochemical tests in our previous study were studied for their decolorising efficiency on various remazol reactive dyes (Remazol Blue RGB, Remazol Blue RR, Remazol Navy RGB and Remazol Orange RR). The synthetic dyes showed complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Bacillus, Ochrobactrum, Clostridium and Pseudomonas covered almost equal percent (14-16%) of 0.05 dominance compare to other strains after 40 days of operation. Previous studies were in agreement with the strains reported in the present study such Bacillus (Shaikh et al 2016), Clostridium (Ekambaram et al 2016) and Pseudomonas (Jayaprakash et al 2016) to treat dye wastewater in MFC. Ochrobactrum was reported as dominant strain by Jayashree et al (2015) in continuous upflow MFC to treat retting pond wastewater.…”
Section: Bacterial Community Analysissupporting
confidence: 93%
“…Bacillus, Ochrobactrum, Clostridium and Pseudomonas covered almost equal percent (14-16%) of 0.05 dominance compare to other strains after 40 days of operation. Previous studies were in agreement with the strains reported in the present study such Bacillus (Shaikh et al 2016), Clostridium (Ekambaram et al 2016) and Pseudomonas (Jayaprakash et al 2016) to treat dye wastewater in MFC. Ochrobactrum was reported as dominant strain by Jayashree et al (2015) in continuous upflow MFC to treat retting pond wastewater.…”
Section: Bacterial Community Analysissupporting
confidence: 93%
“…Clostridium sp. was reported to achieve complete decolorization of Remazol reactive dyes after 24–72 h [ 30 ]. Alkalibaculum sp.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of RN with γ‐Al 2 O 3 /Fe 3 O 4 /SiO 2 /PGMA nanocomposite polymer particles was evaluated by recording FTIR spectra of the adsorbent materials before and after adsorption. In the FTIR spectrum of RN dye (Figure ), the broad signal at 3438 cm −1 represents –NH stretching vibration, sharp signal at 1611 cm −1 represents N=N stretching vibration of azo compounds, signal at 1481 cm −1 represents N‐H trans stretching of secondary amides, signal at 1130 cm −1 corresponds to S=O asymmetric stretching of sulfones and signals at 720 and 618 cm −1 correspond to C–H bending vibrations . The spectrum of γ ‐ Al 2 O 3 /Fe 3 O 4 /SiO 2 /PGMA nanocomposite polymer particles before dye adsorption shows strong absorption signals at 1729.10 and 1153.40 cm −1 for C=O and C–O stretching vibrations of ester group, weak absorption bands at around 958 and 848 cm −1 for epoxide group, absorption signal at 2930 cm −1 for aliphatic C‐H stretching vibration and bands at 1630 and 3435 cm −1 for H–O–H stretching and bending vibrations .…”
Section: Resultsmentioning
confidence: 99%